Transformational Processes of Logistics Activities of Corporate Enterprises in Integration with the Digital Economy - Hutsaliuk, O.; Bondar, Iu.; Kravchenko, M. (Економічний вісник Донбасу, 2023)
The article is devoted to defining the transformational processes of logistics activities of corporate enterprises. The financial and economic factors of increasing the investment attractiveness of transport and logistics enterprises of corporate associations are determined. The approach to evaluating the effectiveness of innovative activities in transport is substantiated, the use of which made it possible to establish the state of regulatory processes in this area, the system of support for decision-making and goal setting, institutional support, and the development of international transport and logistics infrastructure is proposed.
The state of transport security in the regions is determined, the organizational model of the National Innovative Transport Hub and an approach to assessing its functioning are proposed. Proposals are provided for diagnosing the investment attractiveness of transport infrastructure objects, selecting priority projects for state funding and forming public-private partnership models for the innovative development of transport infrastructure. An investment strategy is being developed, which is developed on the basis of the formed investment policy of the enterprise, the essence and direction of which is to choose the most rational ways of preserving and expanding the production potential.
It should be noted that the investment strategy of transport enterprises is one of the most important components of strategic management and consists in the development of a system of measures coordinated in terms of time, resources and performers and aimed at obtaining profit by investing in the most promising, from the point of view of the market situation, spheres of activity of transport enterprises and is a tool for solving the economic problems of domestic transport enterprises is the introduction of innovations and investments. It was determined that the implementation of such sustainability of innovations and investments will improve the economic status of corporate associations of the transport industry, both high-tech and low-tech, providing potential opportunities for increasing economic indicators. Стаття присвячена визначенню трансформаційним процесам логістичної діяльності корпоративних підприємств. Визначено фінансово-економічні фактори підвищення інвестиційної привабливості транспортно-логістичних підприємств корпоративних обєднань. Обґрунтовано підхід до оцінки ефективності інноваційної діяльності на транспорті, використання якого дозволило встановити стан процесів регулювання у цій сфері, системи підтримки прийняття рішень та цілепокладання, інституційного забезпечення запропоновано розвиток міжнародної транспортно-логістичної інфраструктури.
Визначено стан транспортної безпеки регіонів, запропоновано організаційну модель Національного інноваційного транспортного ХАБу та підхід до оцінки його функціонування. Надано пропозиції щодо діагностики інвестиційної привабливості об’єктів транспортної інфраструктури, відбору пріоритетних проектів для державного фінансування та формування моделей державно-приватного партнерства для інноваційного розвитку транспортної інфраструктури. Розробляється інвестиційна стратегія, яка розробляється на основі сформованої інвестиційної політики підприємства, суть і спрямованість якої полягає у виборі найбільш раціональних шляхів збереження та розширення виробничого потенціалу.
Слід зазначити, що інвестиційна стратегія транспортних підприємств є однією з найважливіших складових стратегічного управління і полягає в розробці системи заходів, узгоджених за часом, ресурсами та виконавцями і спрямованих на отримання прибутку шляхом інвестування в найбільш перспективні, з точки зору ринкової кон'юнктури, сфери діяльності транспортних підприємств та є інструментом вирішення економічних проблем вітчизняних транспортних підприємств є впровадження інновацій та інвестицій. Визначено, що реалізація такої стійкості інновацій та інвестицій дозволить підвищити економічний стан корпоративнох обєднань транспортної галузі, як високотехнологічних, так і низькотехнологічних, надаючи потенційні можливості для підвищення економічних показників.